Increasing economic benefit from apiculture through value chain development approach: the case of Alaba special district, Southern Ethiopia - Shiferaw, A.; Jaleta, Moti; Gebremedhin, Berhanu; Hoekstra, Dirk (2010)
In 2005 the IPMS project introduced a participatory market oriented value chain approach in Alaba and apiculture was identified as one of the priority marketable commodities. Amongst the problems and potentials identified in the apiculture value chain were lack of knowledge and skills to operate the modern beehives, low occupancy rate, lack of bee forage and a government controlled technology driven development approach. Furthermore, there was no marketing/processing system for the honey produced from the modern hives. Initial emphasis was given to build capacity and skills on different aspect of apiculture development with follow up and supervisory visits to targeted farmers in two PAs (Peasant associations). Those farmers also benefited from innovative credit channeled through the Menchone farmers’ Union, which enabled them to own more than three modern beehives per household. Linkages were also made with local carpenters for the construction and supply of modern and transitional hives. To alleviate bee forage problems, new forage were introduced in FTCs (Farmers Training Centers) and farmers’ fields. Finally colony splitting was introduced to increase the availability of productive colonies.